(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Language varies according to context, audience, and purpose. These variations manifest through styles, registers, and genres, each playing a crucial role in communication. This article explores the distinctions and interconnections among these linguistic concepts, examining their functions, characteristics, and significance in different communicative settings. By understanding styles, registers, and genres, we can appreciate the adaptability of language and its role in shaping discourse across various domains.